Pengaruh Fear Of Missing Out (FOMO) terhadap Social Connectedness pada Emerging Adulthood - Naufal Rizky Darmansyah; Indri Utami Sumaryanti (Bandung Conference Series: Psychology Science, 2022)
Abstract. Physical distancing policies during the pandemic have had an impact on reducing feelings of social connectedness in emerging adulthood. The use of social media is one of their alternatives to stay connected. However, excessive use of social media can lead to FoMO. Not necessarily negative FoMO can on some occasions encourage a person's feelings of social connectedness. This study aims to determine how the effect of Fear of Missing Out (FoMO) on Social Connectedness on Emerging Adulthood Instagram social media users. The sample obtained is 300 emerging adults aged 18 to 25 years who have used Instagram social media for at least the last 12 months or one year. In this study the research method used is a quantitative method that uses an online questionnaire as a research instrument and the data analysis used is simple linear regression analysis. This study uses the Fear of Missing Out Scale which was developed by Przybylski, et al. (2013) adapted by Azmi (2019) and Social Connectedness Scale-Revised developed by Lee, R., Draper, M., & Lee, S. (2001) adapted by researchers and supervisors. The results in this study indicate that there is a significant and negative effect between FoMO and Social Connectedness in emerging adults in Bandung City with a significance value of .000 and Fear of Missing Out can explain Social Connectedness of 12.2% and 87.2% is explained by the variables others not investigated. Abstrak. Kebijakan jarak fisik selama pandemi telah berdampak pada penurunan perasaan keterhubungan sosial pada emerging adulthood. Penggunaan media sosial menjadi salah satu alternatif mereka untuk tetap terhubung. Namun, penggunaan media sosial yang berlebihan dapat menyebabkan FoMO. Tidak selalu negatif, FoMO pada bebeapa kesempatan dapat mendorong perasaan keterhubungan sosial seseorang. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh Fear of Missing Out (FoMO) terhadap Social Connectedness pada Emerging Adulthood pengguna social media Instagram. Sampel yang diperoleh berjumlah 300 emerging adulthood berusia 18 hingga 25 tahun yang telah menggunakan social media Instagram selama minimal 12 bulan atau satu tahun terakhir. Dalam penelitian ini metode penelitian yang digunakan adalah metode kuantitatif yang menggunakan kuesioner online sebagai instrumen penelitian serta analisis data yang digunakan adalah analisis regresi linear sederhana. Penelitian ini menggunakan alat ukur Fear of Missing Out Scale yang dikembangkan oleh Przybylski, et al. (2013) yang diadaptasi oleh Azmi (2019) dan Social Connectedness Scale-Revised yang dikembangkan oleh Lee, R., Draper, M., & Lee, S. (2001) yang diadaptasi oleh peneliti dan dosen pembimbing. Hasil dalam penelitian ini menunjukkan bahwa adanya pengaruh yang signifikan dan negatif antara FoMO dengan Social Connectedness pada emerging adulthood di Kota Bandung dengan nilai signifikansi .000 dan Fear of Missing Out dapat menjelaskan Social Connectedness sebesar 12.2% dan 87.2 % dijelaskan oleh variabel lain yang tidak diteliti.